Annual Plan 2003-2004 Daman and Diu - Planning Commission (Planning Commission, 2003)
Encouragement to non-polluting small and medium scale industries were given priority in view of liberalised economic policy declared by the Government of India as a result some private Industrial Estates were came up in Dabhel, Kachigam and Bhimpore Panchayats area. The Govt. Industrial Estates set up prior to delinking by the Goa Daman and Diu Industrial Development Corporation were continued to be developed by the Administration giving all services to the entrepreneurs through the District Industries Center which was set up during Ninth Plan. At present there are total 1740 units including Large and Medium Scale Industrial units which provide employment to over 44,000 workers in addition to the indirect employment to the persons engaged in construction activities, transportation and other local traders. This has improved the economic conditions of the local workers.
Union Territory of Daman and Diu, Department of Planning and Statistics